Strategy of pre-emptive management of Epstein-Barr virus post-transplant lymphoproliferative disorder after stem cell transplantation: results of European transplant centers survey - Gil, Lidia; Styczyński, Jan; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Epstein-Barr virus-related post-transplant lymphoproliferative disorder (EBV-PTLD) is a serious complication after stem cell transplantation (SCT) and the number of patients at risk is increasing over time. Available data do not reflect general practice of diagnosis and treatment of this complication. Material and methods: In 2009 a survey on management of the pre-emptive strategy of EBV infection was done and results from 74 European transplant centers were registered and analyzed. Results: Regular monitoring for EBV after SCT is done by most of the participating centers (73%). In 68% of them the monitoring is performed in all alloSCT patients, while in remaining centers it is done in high-risk patients only. Quantitative EBV-DNA is performed in 97% of centers, mainly in whole blood (78%) and usually repeated once a week (60.9%). The monitoring for EBV reactivation is performed for a period of 3 months (37%) to 6 months (30%) or adjusted to risk factors (20%). Rituximab as a pre-emptive therapy for EBV-PTLD is routinely administered in 80% of responding centers. The number of EBV-DNA copies as an indicator for pre-emptive therapy with rituximab varies between the centers. Conclusions: The strategy of management of EBV infection exists in most of the responding centers. Different approaches regarding indications for preemptive therapy are seen between centers: rituximab is administered as preemptive therapy in most participating transplant centers.